The Influence of Recruitment, Work-Life Balance, and Organizational Culture on Organizational Commitment (Case Study: Taman Bunga Celosia Employees) - Windharti, Nicken Reza; Rahayu, Sri; Nurmiyati, Nurmiyati (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to analyze the influence of recruitment, work-life balance, and organizational culture on organizational commitment among employees of Taman Bunga Celosia Bandungan. The research background arises from indications of low organizational commitment, which is presumed to be affected by recruitment practices that are not yet fully competency-based, limited work-life balance policies, and a hierarchical organizational culture. This study employs an associative quantitative approach with a sample of 124 respondents selected through simple random sampling. Data were collected using a Likert-scale questionnaire and analyzed through simple and multiple linear regression using SPSS 25. The results indicate that recruitment, work-life balance, and organizational culture each have a positive and significant effect on organizational commitment. Simultaneously, these three variables also exhibit a significant influence, contributing 67.7% to organizational commitment, while the remaining 32.3% is affected by other factors outside the research model. These findings highlight the importance of transparent recruitment practices, adequate work–life balance policies, and an adaptive organizational culture in enhancing employee commitment.